تقنين أنشطة التحمل الهوائية مصاحبة لنظام غذائي قليل الكربوهيدرات في عملية خفض الوزن الزائد وتحسين اللياقة القلبية التنفسية - عبد الوهاب عبد الرحمن (My University, 2017)
Title: Standardization of aerobic endurance activities linked to a low carbohydrate diet on weight reduction and cardio respiratory fitness. The study aims to determine the impact of the effectiveness of the combination of physical activity with a healthy diet rather than one of them in the process of reducing excess weight with the improvement of cardio respiratory fitness for secondary school age (35-45 years), where then the design and application of a standardized sports program depends on aerobic endurance activities and a specific healthy diet only to reduce carbohydrates consumed, and the work requires a deliberate sample of 30 teachers divided into three experimental groups (03) are overweight, resulting in physical inactivity and consumption Excessive and irrational. The study requires an experimental method to achieve the objectives of the research, on the theory side we use four chapters of, a physical activity, including aerobic endurance activities, nutrition and lobesite, and the overpopulates the characteristics of this phase of age groups, followed by field procedures that we have dealt with a range of anthropometric measures and functional tests and we have processed by SPSS statistical means. through the analysis of the data it is noted that the sample that combines a diet with a sport program designed by the researcher obtained results determined by the weight reduction compared to the first two samples followed the diet and the second athlete program, and it became apparent that they had obtained the results less sample efficiency depending on the merger appeared. in addition there is an improvement in terms of cardio respiratory fitness, the same antenna endurance of these activities has contributed to the improvement of the physical and physiological efficiency because of their direct impact on the body organs such as improvement of work of heart and lungs, especially at this age.
Keywords: aerobic endurance program - diet - weight reduction - cardio respiratory quality.